Refeeding Postmolting Method to Improve Weekly Production Performance of Rejected Laying Hens with Low Mortality - Claude Mona Airin; Amelia Hana; Pudji Astuti; Sarmin Sarmin; Trini Susmiati; Okti Herawati (Faculty of Animal Science, Universitas Gadjah Mada, 2020)
This research aimed to investigate the influence of gradually feeding rejected laying hens after molting on the performance of production. This research used 6,000 rejected laying hens of 80 weeks old in Subur Farm. Molting method was a modification method by reducing the feed gradually. At the beginning of this research, the feed was given 120 g/laying hens/day and it would be reduced by 10 g/laying hens/day until it reach 50 g/laying hens/day. In the next phase, all chickens fasted for seven days then the chicken was given 10 g/laying hens on the first day. The feed was increased 10 g/laying hens every two days up to 120 g/laying hens/day. Data Collection of Feed conversion ratio (FCR), mortality rate, amount of feed, and egg production were taken at the start of re-feeding. The results showed that during the period of molting until refeeding, mortality was 3.6%, an increase in egg production was seen since week 1, peak of production was 78% at week 9 with FCR 2.3. The results of statistical analysis showed significant differences (P<0.05) on the percentage of egg production between time periods after the treatment of feed reduction. As the conclusion, molting followed by refeeding in rejected laying hen influences weekly production performance by extending peak production period, optimal FCR and daily egg production.